Participation lost in translation? : an assessment of local participation during the operational phase of nature reserves - Widmark, Hugo (SLU/Dept. of Urban and Rural Development, 2018)
This master thesis explores how the County Administration Boards (CAB) in Halland, Uppsala and Västerbotten describe how they work with local participation during the operational phase of already established nature reserves. The empirical material consists of reserve decisions and management plans from 186 nature reserves and interviews with CAB officials. When assessing the reserve decisions and management plans, three categories of local participation were discerned: i) local participation as practical management, ii) local participation as consultation, iii) and local participation through management boards. Based on the assessment of the steering documents and the interviews local participation mostly seems to occur through practical management. Management boards and projects with various degrees of dialogue were found in a handful nature reserves. The CABs seem to have a pragmatic view of local participation. If local actors are to be more active in decision making during the management of nature reserves, the CABs need to facilitate and institutionalise such possibilities for local actors.